2018
DOI: 10.1177/1078155218792698
|View full text |Cite
|
Sign up to set email alerts
|

Overuse and underuse of pegfilgrastim for primary prophylaxis of febrile neutropenia

Abstract: Introduction Guidelines recommend pegfilgrastim for primary prophylaxis of febrile neutropenia after highly myelosuppressive chemotherapy. While deviations from guidelines could result in overuse and increased costs, underuse is also a concern and could compromise quality of care. Our objectives were to evaluate guideline adherence and quantify the extent to which physician heterogeneity may influence pegfilgrastim use. Methods We randomly sampled 550 patients from a retrospective cohort of those who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Likewise, in a study conducted by Zullo et al in the United States, nine out of 15 patients who were treated with a chemotherapy regimen with high FN risk did not receive G-CSF. 21 This is while all patients with high FN risk in our study received prophylactic G-CSF. Of note, G-CSF was administered to 60 (62%) patients with no indication and over utilization was a more important inconsistency with the guideline recommendations in our study.…”
Section: Discussionmentioning
confidence: 90%
“…Likewise, in a study conducted by Zullo et al in the United States, nine out of 15 patients who were treated with a chemotherapy regimen with high FN risk did not receive G-CSF. 21 This is while all patients with high FN risk in our study received prophylactic G-CSF. Of note, G-CSF was administered to 60 (62%) patients with no indication and over utilization was a more important inconsistency with the guideline recommendations in our study.…”
Section: Discussionmentioning
confidence: 90%
“…A retrospective study assessed pegfilgrastim use in four outpatient sites of the Lifespan Comprehensive Cancer Centre (USA). 17 The study found that pegfilgrastim, predominantly as primary prophylaxis, was prescribed when the chemotherapy used had a risk of FN of ≥20%. Interestingly, filgrastim was rarely used.…”
Section: Primary Prophylaxis Preferencementioning
confidence: 99%
“…In fact, various studies have shown that G-CSFs tend to be overused in patients administered low-risk chemotherapies (risk of FN <10% or 10%-20%) and underused in those on high-risk regimens (risk of FN >20%). [17][18][19] Indeed, the use of G-CSFs in clinical practice, as primary and secondary prophylaxes, is driven by various factors including the convenience and cost of G-CSFs, availability of biosimilars and the clinical evidence for the benefit of G-CSFs. 14 A better understanding of the factors that influence the choice of G-CSF will allow optimisation of G-CSF use in clinical practice and consequently improve FN management in patients with cancer .…”
Section: What Are the New Findings?mentioning
confidence: 99%
“…Significant underuse of G‐CSFs in high‐ and intermediate‐risk regimens, and overuse in low‐risk regimens, have been reported both in the EU 4,5 and in the US 6‐8 . G‐CSFs contribute also significantly to increased healthcare costs 9 .…”
Section: Introductionmentioning
confidence: 99%